Literature Review Implementasi Interprofessional Education (IPE) Dan Interprofessional Collaboration (IPC) Di SMK Kesehatan: Peluang Dan Strategi Kolaborasi Interprofesi Dalam Lingkungan Pendidikan Kejuruan Kesehatan - Siti Zahara Nasution; Sovie Ramadhanty Silalahi; Evi Karota Bukit; Rika Endah Nurhidayah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Interprofessional Education (IPE) and Interprofessional Collaboration (IPC) are two major pillars of modern health workforce education reform recommended by the World Health Organization since 2010. Although their implementation has rapidly developed in higher health education institutions, the application of IPE and IPC in Indonesian Vocational High Schools of Health (SMK Kesehatan) remains limited. This literature review examines the concepts, theoretical foundations, empirical evidence, barriers, opportunities, and implementation strategies of IPE and IPC within the context of SMK Kesehatan. The method used was a narrative literature review by analyzing articles from PubMed, Cochrane, CINAHL, Springer, Google Scholar, and SINTA databases published between 2010 and 2024. The findings indicate that IPE has been proven to improve collaborative competencies, interprofessional communication, and students’ work readiness. SMK Kesehatan possesses significant strategic opportunities to integrate IPE through the diversity of health-related study programs within one institution, practice-oriented learning approaches, and partnerships with healthcare facilities. The major barriers include curriculum fragmentation, limited availability of IPE facilitators, and differences in professional identity. Recommended strategies include integrating IPE into the Merdeka Curriculum, establishing cross-disciplinary facilitator teams, and developing interprofessional simulation modules based on clinical contexts.